Impact of the Neck and/or Shoulder Pain on Self-reported Headache Treatment Responses – Results From a Pharmacy-Based Patient Survey - Gaul, Charly; Gräter, Heidemarie; Weiser, Thomas; Michel, Martin C.; Lampert, Anette; Plomer, Manuel; Förderreuther, Stefanie (Frontiers in Neurology, 2022)
Neck and/or shoulder pain (NSP) frequently occurs together with headache. Therefore, we explored how patients with and without concomitant NSP differ in their baseline characteristics and in perceived treatment responses to an analgesic. An anonymous survey was performed among 895 patients with headache (735 self-reported tension-type headache [TTH]) who used an analgesic fixed-dose combination containing 400 mg ibuprofen and 100 mg caffeine as a non-prescription treatment. NSP was abundant among patients in our survey (60%) and was associated with >1 additional day of headache per month. Patients with NSP reported predominantly sedentary work more frequently than those without (40 vs. 29%); they also reported physical tension/poor posture as a perceived trigger factor more frequently (70 vs. 16%). The reported pain reduction was comparable in those with and without concomitant NSP regardless of whether assessed as mean pain rating (from about 6 to 1.5 on a 10-point rating scale), patients experiencing a ≥50% in pain reduction (89.6 vs. 88.8%) or becoming pain-free within 2 h (57 vs. 64%). However, recurrence of pain and use of another dose within the same day were more frequent with than without NSP. We conclude that concomitant NSP is frequent in patients with headache but does not substantially alter responses to a non-prescription medication.